Pengaruh Gadget terhadap Motivasi Belajar Siswa - Nisaul Hanifa; Sartono Sartono (STIKes Ibnu Sina Ajibarang, 2025)
The use of gadgets is increasingly widespread among elementary and middle school students, bringing various impacts on their learning motivation and psychosocial development. This article reviews literature related to the positive and negative effects of gadget use on school-aged children. The review results show that gadgets used as learning media can significantly enhance student participation and interest in learning. However, excessive use of gadgets for non-educational activities, such as gaming and social media, can lead to psychosocial disturbances, including difficulties in socializing, decreased learning motivation, and health issues such as sleep disorders and reduced concentration. Therefore, supervision and guidance from teachers and parents are essential so that gadgets can be optimally utilized to support the learning process and children's development.